Does Information and Deliberation Affect Ecosystem Service Judgments? Evidence from Tree Plantation Expansion in Argentina. Issue 11 (2nd November 2021) - Sanders, A. Renee; Nielsen, Erik A.; Abrams, Jesse
Abstract: Non-native tree plantations have become a significant presence on the landscape of northeastern Argentina. This study investigated perceptions of eucalyptus plantations in two Argentine communities: Ubajay, a community with significant historical plantation presence and forestry industry employment, and La Criolla, a community transitioning to a greater focus on plantation forestry. The purpose of this study was to determine effects of providing scientific results to community members and facilitating discourse on participant judgments of plantations' ecosystem service effects and the acceptability of plantations as a land use. Following information provision and discussion, La Criolla participants judged plantation impacts more negatively than did their Ubajay counterparts. Our findings suggest that ecosystem service impacts are likely to be judged less negatively by those who receive socioeconomic benefits from plantations. Analysis of these changing community judgments emphasizes the importance of engaging the public with deliberative practices and exposure to the best available scientific information.